An Overview of Hydrogen Production: Current Status, Potential, and Challenges. (15th May 2022) - Younas, Muhammad; Shafique, Sumeer; Hafeez, Ainy; Javed, Fahad; Rehman, Fahad
Graphical abstract: Highlights: Hydrogen production pathways via renewable and non-renewable sources. Renewable energy sources gaining potential as clean energy source to produce H2. Plasmolysis is competitive to electrolysis for H2 production. Plasmolysis is beneficial for its low power consumption and reduced equipment size. Solar integrated plasmolysis with zero carbon footprints is the proposed strategy. Abstract: Hydrogen as an energy carrier can provide a long term solution to the problem of sustainable supply of cleaner and environmentally friendly fuel. Hydrogen finds extensive use s in petroleum, chemical synthesis and treated as a zero-emission fuel for transportation as well. It could also be used to produce power. Especially, in the remote areas away from main cities where electrification cost would be significantly higher. A hydrogen based decenteralized system could be developed where the "surplus" power generated by a renewable source could be stored as chemical energy in the form of hydrogen. 80% of the whole hydrogen produced is by steam methan reforming at an energy efficiency of 74–85%. However, steam methane reforming and other fossil fuel based technologies are neither green nor sustainable. Hydrogen, could only be counted as a renewable and clean fuel if the required power to produce hydrogen comes from a renewable source such as wind or solar power. Using a renewable source, hydrogen could be produced by electrolysis, biohydrogen, thermochemical cycles, photocatalysis, and plasmolysis. Amongst hydrogen production technologies, electrolysis contributes the highest 4% of the total world's energy demand. The production cost and energy efficiency estimated for electrolysis are 10.3 /kg and 52%, respectively. Electrolysis, an energy-intensive process for hydrogen production, is still confronting challenges to manifest itself economically. While, the production rate of 20 g/kWh with predicated cost and efficiency 0.09 €/kWh or 6.36 /kg and 79.2%, respectively, has been reported that depicts plasmolysis competitive on par with electrolysis with the advantage of low power consumption, reduced equipment size and principle cost. This review highlights the current status, potential, and challenges of both renewable and non-renewable hydrogen production. A new strategy for simultaneous hydrogen production and separation by microplasmas and microbubble mediated mass transfer has been proposed. A decenterlaized system for hydrogen generation by combining the proposed strategy with solar energy has been suggested to reduce the carbon footprints.